A Call for Research on the Scaling of Organizations and the Scaling of Social Impact. (March 2022) - Shepherd, Dean A.; Patzelt, Holger
Although scaling is a "hot topic" in the practitioner literature, it has largely been ignored (at least explicitly) in the academic literature. This editorial highlights the importance of organizational scaling, which we define as "spreading excellence within an organization as it grows." Specifically, the entrepreneurship field would benefit greatly from future studies that explain how knowledge management facilitates scaling; how scaling is influenced by founder replacement; and how current scaling influences the drivers of subsequent scaling. We eventually link the scaling of organizations to the scaling of social impact.